Angiogenesis inhibition in lung cancer: emerging novel strategies. Issue 1 (22nd January 2022) - Lazzari, Chiara; Bulotta, Alessandra; Damiano, Giuseppe; Mirabile, Aurora; Viganó, Mariagrazia; Veronesi, Giulia; Gregorc, Vanesa
Abstract : Purpose of review: In the current review, we will explore the molecular bases that have determined the design of clinical trials exploring the efficacy of antivascular agents in combination with chemotherapy, immune check point inhibitors and epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in patients with advanced nonsmall cell lung cancer. Recent findings: Recent clinical trials have demonstrated the synergistic effect of antivascular agents with immune checkpoint inhibitors and EGFR-TKIs, despite no molecular marker has been identified yet to select patients. Summary: Lung cancer remains one of the first causes of cancer-related death. However, thanks to the development of stratified molecular medicine and the introduction of immune checkpoint inhibitors, patients' survival has significantly improved. Due to the critical role of pro-angiogenic factors in cancer progression, antivascular agents targeting the vascular endothelial growth factor (VEGF) and its receptor (VEGFR) have been developed. Their efficacy has been explored in combination with chemotherapy, and immune checkpoint inhibitors, with promising but not definitive conclusions about their impact on prolonging patients' survival.